PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DEVISIONS (STAD) TERHADAP HASIL BELAJAR KOGNITIF PESERTA DIDIK KELAS X SMA YPK OIKOUMENE MANOKWARI PADA REAKSI REDOKS - Orgenes Moses Kapisa (Universitas Papua, Manokwari, Indonesia, 2021)
Abstact YPK Oikoumene Manokwari High School is one of the private schools located in Manokwari. This high school has implemented the 2013 curriculum with adequate facilities and infrastructure. The learning model used is still using conventional teacher-centered learning models so that students feel bored with the learning process that affects student learning outcomes. Cooperative learning model type Student Teams Achievement Divisions (STAD) which involves many students in studying the material covered in a lesson and checking their understanding of the content of the lesson. Based on the results of the research obtained on the cooperative learning model of the Student Teams Achievement Divisions (STAD) type on the cognitive learning outcomes of students, the Standard Gain results obtained with a value of 0.64 so that it can be said to have a moderate effect. The percentage of the effect obtained is 50% which shows that the cooperative learning model of the Student Teams Achievement Divisions (STAD) type has a fairly good influence on the learning outcomes of students in class X IPS SMA YPK Oikoumene Manokwari. Keywords: Cognitive Learning, Redox Reaction, Student Teams Achievement Divisions (STAD